Large reduction of thermal conductivity leading to enhanced thermoelectric performance in p-type Mg3Bi2–YbMg2Bi2 solid solutions. Issue 2 (19th December 2018) - Zhou, Ting; Mao, Jun; Jiang, Jing; Song, Shaowei; Zhu, Hangtian; Zhu, Qing; Zhang, Qinyong; Ren, Wuyang; Wang, Zhiming; Wang, Chao; Ren, Zhifeng
Abstract : The thermoelectric property of YbMg2 Bi2 –Mg3 Bi2 solid solution is studied. Abstract : Intensifying the phonon scattering via point defect engineering has been demonstrated to be particularly effective in minimizing the lattice thermal conductivity for enhancing thermoelectric performance. In this work, significant phonon scattering has been realized by alloying YbMg2 Bi2 with Mg3 Bi2 . The substantial mass difference between the host atom Yb and the alloying atom Mg leads to an intense phonon scattering effect that significantly reduces the lattice thermal conductivity. The room-temperature lattice thermal conductivity decreases from ∼2.7 W m −1 K −1 for YbMg2 Bi1.96 to ∼0.8 W m −1 K −1 for Yb0.7 Mg0.3 Mg2 Bi1.96, a reduction of ∼70%. Benefiting from the greatly reduced thermal conductivity, the average ZT has been effectively improved from ∼0.46 for YbMg2 Bi1.96 to ∼0.61 for Yb0.8 Mg0.2 Mg2 Bi1.96, an enhancement of ∼33%. In addition, the predicted maximum heat-to-electricity conversion efficiency can be increased from ∼7% for YbMg2 Bi1.96 to ∼10% for Yb0.8 Mg0.2 Mg2 Bi1.96 .